2017
DOI: 10.7554/elife.29944
|View full text |Cite
|
Sign up to set email alerts
|

A new genus of horse from Pleistocene North America

Abstract: The extinct ‘New World stilt-legged’, or NWSL, equids constitute a perplexing group of Pleistocene horses endemic to North America. Their slender distal limb bones resemble those of Asiatic asses, such as the Persian onager. Previous palaeogenetic studies, however, have suggested a closer relationship to caballine horses than to Asiatic asses. Here, we report complete mitochondrial and partial nuclear genomes from NWSL equids from across their geographic range. Although multiple NWSL equid species have been na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 80 publications
(191 reference statements)
10
71
1
1
Order By: Relevance
“…These characteristics of ancient DNA and practices used in palaeogenomic studies make them particularly vulnerable to reference bias (Prüfer et al ., 2010; Schubert et al ., 2012). It has been shown that pseudo-haploid data can be more biased than imputed genotypes (Martiniano et al ., 2017), and that reference bias and fragment length artifacts can interfere with phylogenetic classifications (Heintzman et al ., 2017). Reference bias can influence downstream analyses if these are based on estimating allele frequencies in a population, or studying pairwise allele sharing between individuals and groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics of ancient DNA and practices used in palaeogenomic studies make them particularly vulnerable to reference bias (Prüfer et al ., 2010; Schubert et al ., 2012). It has been shown that pseudo-haploid data can be more biased than imputed genotypes (Martiniano et al ., 2017), and that reference bias and fragment length artifacts can interfere with phylogenetic classifications (Heintzman et al ., 2017). Reference bias can influence downstream analyses if these are based on estimating allele frequencies in a population, or studying pairwise allele sharing between individuals and groups.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing reads carrying an alternative allele will naturally have mismatches in the alignment to the reference genome and consequently have lower mapping scores than reads carrying the same allele as the reference. This effect increases with genetic distance from the reference genome, which is of particular interest when using a reference genome from a related species for mapping (Shapiro and Hofreiter, 2014; Gopalakrishnan et al, 2017; Heintzman et al, 2017). Generally, reference bias can influence variant calling by missing alternative alleles or by wrongly calling heterozygous sites as homozygous reference (Bobo et al, 2016; Ros-Freixedes et al, 2018) which is known to influence estimates of heterozygosity and allele frequencies (Chen et al, 2012; Bryc et al, 2013; Brandt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, new approaches to age-depth modeling provide better estimates of temporal certainty for unsampled portions of sedimentary deposits (Buck et al 1999, Haslett and Parnell 2008, Bronk Ramsey 2009, Blaauw and Christeny 2011. Second, ancient DNA has been crucial for improving our ability to obtain species-level identifications from fossil assemblages (Heintzman et al 2017) and extending the variety of taxa that could be sampled from sedimentary deposits (Pedersen et al 2015).…”
Section: Inferring Assemblage-level Processes In Space and Time: Datamentioning
confidence: 99%
“…Since we evaluated morphological characters of teeth and bones of fossil horses from southern Mexico and to avoid the unnecessary proliferation of names for the Mexican equid species, we follow the taxonomic scheme of Priego-Vargas et al (2017, table 10) that recognized four Pleistocene Equus species for Mexico: Equus conversidens, E. mexicanus, E. francisci, and E. cedralensis. Since Heintzman et al (2017) transferred E. francisci to Haringtonhippus, instead of E. francisci, we used the name H. francisci.…”
Section: Studied Specimensmentioning
confidence: 99%
“…By means of paleogenomic and morphometric analyses, a new genus of NWSL horse for the Pleistocene of North America was erected: Haringtonhippus francisci. This species was reported (as Equus conversidens) from San Josecito Cave, Nuevo Léon, based upon a short mitochondrial DNA sequence (Barrón-Ortiz et al, 2017); this record was subsumed into H. francisci by Heintzman et al (2017). Finally, Barrón-Ortiz et al (2019) based on a morphology-based tree, determined that Equus comprises eight species, including H. francisci, and suggested that Haringtonhippus should be considered a synonym of Equus, but the authors do not formally synonymize both taxa.…”
Section: Introductionmentioning
confidence: 99%